Safety Climate Evaluation in EPC Company Using The NOSACQ-50 Method and Safety Model Canvas: Evaluasi Iklim Keselamatan Pada Perusahaan EPC Dengan Metode NOSACQ-50 dan Kanvas Model Keselamatan - Naia Putri Harendsa; Mega Cattleya Prameswari Annissaa Islami (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
A good work safety culture can improve occupational safety and health in the work environment. One of the keys to creating safe and sustainable working environment is to raise awareness of the importance of work safety. PT XYZ is a company providing large-scale Engineering, Procurement and Construction (EPC) services. The problem faced is that work accidents still occur so that the company is still unable to achieve the zero-accident target. This study aims to identify the level of safety climate security using the Nordic occupational safety climate questionnaire (NOSACQ-50) and formulate recommendations for appropriate and sustainable improvements using the safety model canvas (SMC). The study results show that four of the seven dimensions of safety climate received scores between 3.00 – 3.30, which shows that improvement and improvements are still needed. Based on the safety canvas model that has been created, the priorities for improving safety climate from the first to the last are responsibility, engagement & involvement, competence, information & communication, risk, commitment, leadership, organizational learning.